Designing ternary blend all-polymer solar cells with an efficiency of over 10% and a fill factor of 78%. (September 2018) - Li, Zhenye; Ying, Lei; Xie, Ruihao; Zhu, Peng; Li, Ning; Zhong, Wenkai; Huang, Fei; Cao, Yong
Abstract: In recent years, ternary blend bulk-heterojunction (BHJ) all-polymer solar cells have been gradually developed to better utilize the solar irradiance spectrum. However, power conversion efficiencies remain below 10%, mainly because of the low fill factor. Generally, the fill factor of all-polymer solar cells is limited mainly by the competition between the recombination and extraction of free charges. Here, we design advanced ternary blend all-polymer solar cells with a high fill factor of 78%, thus demonstrating how such recombination thresholds can be overcome. These results can be attributed to the high and balanced bulk charge mobility, reduced recombination, and optimized morphology, as well as the intimate mixing properties of the two donors in the photoactive layer. Graphical abstract: Highlights: All-polymer solar cells were designed by combining two electron-donating polymers and an electron-accepting polymer. The intimate mixing properties of the two donors enabled the formation of an alloy-like blend in the present ternary systems. The resulting devices exhibited a record high fill factor over 78% and an impressively high power conversion efficiency over 10%.